1996
DOI: 10.1097/00007890-199609270-00020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacterial Endotoxin on Radiation-Induced Activation of Human Endothelial Cells in Vitro and in Vivo

Abstract: Previous work from our group has contributed to demonstrate the role of conditioning related release of proinflammatory cytokines in induction of acute graft-versus-host disease (GVHD) following allogeneic bone marrow transplantation (BMT). In the present report we show that ionizing radiation (IR) in a clinical relevant dose upregulates intercellular adhesion molecule 1 (ICAM-1) on cultured human microvascular endothelial cells (HMEC). Bacterial endotoxin (lipopolysaccharide, LPS) in a concentration correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
3
19
0
1
Order By: Relevance
“…4,7 These properties of IL-10 have led to its use for the treatment of GVHD in several studies, since IL-10 inhibits the activity of antigen-presenting cells and reduces the proliferation of lymphocytes as well as antagonizing lipopolysaccharide, which is involved in the production of inflammatory cytokines. 8,9 However, treatment with IL-10 did not effectively suppress GVHD in these studies and actually aggravated it in some cases, resulting in a poor prognosis because treatment with this cytokine caused rejection. 10,11 We interpreted the results obtained in the present study as follows.…”
Section: Discussionmentioning
confidence: 86%
“…4,7 These properties of IL-10 have led to its use for the treatment of GVHD in several studies, since IL-10 inhibits the activity of antigen-presenting cells and reduces the proliferation of lymphocytes as well as antagonizing lipopolysaccharide, which is involved in the production of inflammatory cytokines. 8,9 However, treatment with IL-10 did not effectively suppress GVHD in these studies and actually aggravated it in some cases, resulting in a poor prognosis because treatment with this cytokine caused rejection. 10,11 We interpreted the results obtained in the present study as follows.…”
Section: Discussionmentioning
confidence: 86%
“…High levels of IL-10 produced prior to BMT may down-regulate tissue expression of ICAM-1 and ICAM-1-mediated transendothelial migration of inflammatory cells which occurs after irradiation or LPS activation. 17,18 In addition, downmodulation of other costimulatory molecules including CD80 on antigen presenting cells such as dendritic cells by IL-10 may result in tolerance. 19 Finally, presence of high IL-10 production at the time of donor cell infusion might induce a host-specific anergic state in donor T lymphocytes as reported in vitro in mixed lymphocyte reactions carried out in the presence of IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown the important role of CAMs in lymphocyte homing to inflamed tissues (2,10,21,22,27,45). Since our studies concentrated on the colon, we focused on the expression of MAdCAM, because it has been demonstrated to be essential in the induction of intestinal GVHD (22).…”
Section: Discussionmentioning
confidence: 99%
“…Irradi- ation has also been shown to stimulate macrophage production of proinflammatory cytokines in a dose-dependent manner (43). Several in vivo and in vitro studies have demonstrated that endothelial cells respond to stimuli such as irradiation, LPS, and TNF-␣ by becoming activated or undergoing apoptosis (21,40). In the SGVHD model, increased bacterial leakage into the liver was observed during CsA therapy, suggesting increased permeability of the colon in these animals (25).…”
Section: Enhanced Cd4mentioning
confidence: 99%
See 1 more Smart Citation